DETERMINASI MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN PADA BENGKEL AUTOTAMA MOBIL MOTOR DI KARANGASEM - Putri Anggreni (STIMI Handayani Denpasar, 2016)
This study will examine the determination of achievement motivation onemployee performance Autotama Car Motor Karangasem. Statistical analysis wasused to test the hypothesis with a simple linear regression. The stages of the analysisconducted in this study is a description of the data. Qualification data descriptionachievement motivation and performance of employees, also using univariantanalysis. This analysis is based on the average score of the ideal (Mi) and the idealstandard deviation (SDI). As well as this analysis also includes testing requirementsanalysis and hypothesis testing. The analysis showed that there was a significantcorrelation between the Achievement Motivation Employee Performance throughthe equation of the line y = -36.800 + 0.632 X with Freg = 43.015 (p <0.05). In thepresent study found a significant correlation between the Achievement MotivationEmployee Performance at 0.691 with p <0.05. These findings indicate thatachievement motivation has an important role in improving employee performance.Normatively found that achievement motivation is very good in the category meansan employee has shown excellent achievement motivation in carrying out his job.From the correlation analysis it is evident that significant determination between theAchievement Motivation Employee Performance. It needs to be maintained to keepemployees comfortable and satisfied in performing everyday tasks so that corporateobjectives will be achieved.